1997
DOI: 10.1590/s0100-879x1997001100005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytotoxic activity on Vero cells in clinical isolates of Serratia marcescens

Abstract: Cytotoxin production was studied in 60 Serratia marcescens strains isolated from hospitalized patients. Association of cytotoxic activity with serotype, source of isolation and presence of plasmids was also evaluated. Thirteen of the 60 S. marcescens strains produced a cytotoxic effect on Vero cells. These strains were isolated from distinct clinical sources and classified into seven different serotypes (O1:H7; O4:NM; O10:NT; O19:NM; O6,14:H4; O6,14:NM and O6,14:H1). No relationship was observed between cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…In general, S. marcescens infections induce inflammation and fever, but fatal bacteremia can develop in patients weakened by previous infection, surgery, or immunosuppression (24,59,64,67). Despite numerous reported S. marcescens infections and the emergence of antibiotic-resistant strains (7,14,23,62), the virulence mechanisms of this organism are poorly understood.Carbonell and coworkers reported that S. marcescens culture filtrates exhibited pronounced in vitro cytotoxicity to cultured mammalian cells (11,12). Importantly, cytotoxicity was detected to various extents in all the strains that were tested, regardless of biotype or serotype (12).…”
mentioning
confidence: 99%
“…In general, S. marcescens infections induce inflammation and fever, but fatal bacteremia can develop in patients weakened by previous infection, surgery, or immunosuppression (24,59,64,67). Despite numerous reported S. marcescens infections and the emergence of antibiotic-resistant strains (7,14,23,62), the virulence mechanisms of this organism are poorly understood.Carbonell and coworkers reported that S. marcescens culture filtrates exhibited pronounced in vitro cytotoxicity to cultured mammalian cells (11,12). Importantly, cytotoxicity was detected to various extents in all the strains that were tested, regardless of biotype or serotype (12).…”
mentioning
confidence: 99%
“…The parasites were grown and maintained as reported previously [17]. THP-1 and Vero cells (ATCC) were cultured as reported previously by Gebre-Hiwot and colleagues [18] also Carbonell and colleagues [19], respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity assay was performed as described by Konowalchuk and colleagues [22] as well as Carbonell and colleagues [19] with some modifications. Briefly, confluent monolayers of Vero cells were removed with trypsin EDTA, re-suspended to…”
Section: Methodsmentioning
confidence: 99%
“…Studies of the virulence factors of S. marcescens demonstrated that clinical isolates produce a toxin with activity on Vero (African Green monkey kidney) cells in culture (5). These strains were isolated from distinct clinical sources and no relationship was observed between cytotoxic activity and strain serotype.…”
Section: Introductionmentioning
confidence: 99%
“…The cytopathic effects of the S. marcescens cytotoxin correspond to cell rounding followed by gradual destruction of the monolayer, as observed by inverted microscopy (5). This technique is routinely used to assess cytotoxicity in cell culture; however, it lacks sensitivity for detecting more details about early events of the cell injury process.…”
Section: Introductionmentioning
confidence: 99%